(untitled) (IAHS Medical Journal, 2022)
Background: Umbilical cord act ascable that links the fetus to the placenta. Fetal wellbeing depends much on the normal structure andfunction of umbilical cord. Blood vessels in it connect the uterine vasculature and the fetal vascular tree and are essential part of fetal circulation. A number of structural abnormalities, macroscopic and microscopic, can affect the umbilical cord and the ultimate effect is disturbance of the lifeline & derangement of blood flow to the fetus. Hence, structural changes of umbilical cord have been found to be a marker of intrauterine complications of fetus. The aim of the study is to find out the microscopic abnormalities of human umbilical cord in normal pregnancies. Materials and methods: A descriptive cross sectional study was done in the Department of Anatomy, Chittagong Medical College on 60 human umbilical cord sample from August 2012 to January 2013. Results: Among the 60 samples endothelial erosion was found in 11.7% cases, extravasation of blood within Wharton’s Jelly area was found in 1.7% cases, disruption of muscle layer in tunica media was found in 5% cases, grossly dilated umbilical vein was found in 20% cases, vacuolated space within Wharton’s Jelly area was found in 3.3% cases. Conclusion: In normal pregnancies histological abnormalities of umbilical cord may be present but to a lesser extent. IAHS Medical Journal Vol 5(1), June 2022; 91-93